Overview of molecular subtype of medulloblastoma and role of MRI in their identification - Ashfaq Ahmad; Aisha Islam (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2022)
Medulloblastoma is the most prevalent malignant brain tumor in children, accounting for roughly 15% to 20% of all malignancies of the Central Nervous System (CNS), for 40% of childhood, tumors are in the posterior fossa. Medulloblastoma is a heterogeneous combination of several subgroups with discrete characteristics, rather than a homogeneous illness. Genomic profiling of medulloblastomas revealed that the medulloblastoma may be further divided into four separate molecular subgroups. In this review, we aim to focus on the current state of understanding of the molecularity of the disease with a focus on genomic events that define the aforementioned subgroups and an overview of the molecular subtype of medulloblastoma upon discussing the following points (i) introduction to medulloblastoma and basic classification of the molecular subtype of medulloblastoma followed by their prevalence, age and gender discrimination, and specific molecular characterization. (ii) specific MRI features of the locality of a molecular subtype of medulloblastoma (iii) finally MRI distinguishable features for the identification of the specific molecular type. This review will enhance your knowledge regarding the subtype of medulloblastoma and the role of MRI in the identification of these subtypes.